Association of p53 with Bid Induces Cell Death in Response to Etoposide Treatment in Hepatocellular Carcinoma - Song, G.; Chen, G. G.; Yun, J.-P.; Lai, P. B.S. (Current Cancer Drug Targets, 2009)
Appropriate subcellular localization of proteins is crucial for regulating their functions. Both p53 and the BH3- only Bid play roles in the development and the treatment of hepatocellular carcinoma (HCC). They both participate in the cross talk of cell cycle arrest and apoptosis in response to DNA damage. However, some important issues related to their pathways are not yet resolved. Bid genomic loci contain p53-binding DNA response elements and Bid can mediate p53- dependent transactivation. Here, we showed that etoposide-induced DNA damage could significantly induce p53 and Bid nuclear export. When cells were stimulated by etoposide, p53 could, through the association with Bid, cause translocation of Bid from the nucleus to the cytoplasm and on to its ultimate location in the mitochondria. p53 was physically associated with Bid, and both p53 and Bid cooperatively promoted cell death induced by etoposide. Knockdown of Bid expression notably attenuated cell death induced by etoposide and also released p53 from the mitochondria. These findings reveal a novel mechanism by which p53 is associated with Bid in the nucleus to facilitate exportation of Bid to the mitochondria and induce apoptosis in response to etoposide-induced DNA damage in HCC.
Keywords: mitochondria